2021
DOI: 10.14719/pst.2021.8.2.1007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fungicides, plant extracts and biocontrol agents against Ascochyta blight (Ascochyta rabiei) of chickpea (Cicer arietinum L.) under field conditions

Abstract: Two fungicides, Aliette and ThiovitJet @ 0.15%, containing Aluminum tris (O-ethyl phosphonate) and sulphur compounds, respectively; two plant extracts, Melia azedarach and Azadirachta indica @ 8% and one biocontrol agent, Trichoderma harzianum @ 107 conidia ml-1 were investigated against ascochyta blight of chickpea under field conditions. Treatments were evaluated on three varieties susceptible to chickpea blight. Field trial revealed that Aliette and ThiovitJet significantly decreased disease severity to 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Research conducted for testing several chemicals against A. rabiei, it was noted that chlorothalonil, zineb, captan, antracol, propiconazole, penconazole, and thiabendazole is effective and controlling the spread of Ascochyta blight (Ahmad et al, 2021). Likewise, biocontrol agents, T. viride, Chaetomium globosum, and Acremonium implicatum under In-vitro conditions proven effective against A. rabiei (Bisen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted for testing several chemicals against A. rabiei, it was noted that chlorothalonil, zineb, captan, antracol, propiconazole, penconazole, and thiabendazole is effective and controlling the spread of Ascochyta blight (Ahmad et al, 2021). Likewise, biocontrol agents, T. viride, Chaetomium globosum, and Acremonium implicatum under In-vitro conditions proven effective against A. rabiei (Bisen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some Pseudomonas species produce secondary metabolites (such as pigments and heterocyclic compounds, such as phenazine) which have broad-spectrum antifungal properties. Certain fungal species have also shown promising activity against Ascochyta blight in vitro [ 111 ] ( Table 1 ).…”
Section: Disease Managementmentioning
confidence: 99%
“…Plants themselves produce secondary metabolites that can have antifungal and antimicrobial activity [ 111 , 112 , 113 ]. For this reason, plant extracts and essential oils are being studied as a natural solution to phytopathogenic disease.…”
Section: Disease Managementmentioning
confidence: 99%
“…Burdon and Chilvers 1982;Boudreau and Mundt 1997). Jaccoud-Filho et al(2016) reported that, reduced row spacing increase severity of Sclerotinia sclerotiorum in soybean, while increase row spacing decreased disease severity.Table(2): Interaction between foliar spraying and sowing dates on Ascochyta blight incidence, severity and some growth parameters of pea (average of combined data over 2020/2021 and 2021/2022 seasons)…”
mentioning
confidence: 99%